Individualized model for predicting pathological complete response to neoadjuvant chemotherapy in patients with breast cancer: A multicenter study - Qian, Bei; Yang, Jing; Zhou, Jun; Hu, Longqing; Zhang, Shoupeng; Ren, Min; Qu, Xincai (Frontiers in Endocrinology, 2022)
Background: Pathological complete response (pCR) is considered a surrogate for favorable survival in breast cancer (BC) patients treated with neoadjuvant chemotherapy (NACT), thus is the goal of NACT. This study aimed to develop and validate a nomogram for predicting pCR probability of BC patients after NACT based on the clinicopathological features. Methods: A retrospective analysis of 527 BC patients treated with NACT between January 2018 and December 2021 from two institutions was conducted. Univariate and multivariate logistic regression were performed to select the most useful predictors from the training cohort (n=225), and then a nomogram model was developed. The performance of the nomogram was evaluated with respect to its discrimination, calibration and clinical usefulness. Internal and external validation were performed in independent validation cohort of 96 and 205 consecutive BC patients respectively. Results: Among the eighteen clinicopathological features, five variables were selected to develop the prediction model, including age, AJCC T stage, Ki67 index before NACT, HER2 and HR status. The model showed good discrimination with an AUC of 0.825 (95% CI, 0.772 to 0.878) in the training cohort, 0.755 (95% CI, 0.658 to 0.851) and 0.79 (95% CI, 0.724 to 0.856) in the internal and external validation cohort respectively. The calibration curve presented good agreement between prediction by nomogram and actual observation, and decision curve analysis (DCA) indicated that the nomogram had good net benefits in clinical scenarios. Conclusion: This study constructed a validated nomogram based on age, AJCC T stage, Ki67 index before NACT, HER2 and HR status, which could be noninvasively applied to personalize the prediction of pCR in BC patients treated with NACT.